Hemostatic alterations during extracorporeal membrane oxygenation in ovine veno‐venous and veno‐arterial models. Issue 3 (9th November 2022) - Gao, Sizhe; Zhang, Yang; Peng, Rui; Yan, Shujie; Teng, Yuan; Qi, Jiachen; Cheng, Gaowa; Yu, Dongze; Liu, Gang; Xu, Qiang; Cai, Xiaohui; Zhou, Zhou; et al.
Abstract: Background: Extracorporeal membrane oxygenation (ECMO) has salvaged many people's life during global pandemics. However, ECMO is associated with a high incidence of hemostatic complications. This study aims to explore the effects of the ECMO system on the coagulation system in the healthy ovine ECMO model. Methods: Ten healthy male sheep were included. Five received the veno‐arterial ECMO and five received the veno‐venous ECMO. Heparin was infused for systemic anticoagulation and was adjusted according to the activated clotting time. Blood routine tests, coagulation factors, anticoagulation proteins, and fibrinolysis markers were tested at the baseline and every 24 h. After weaning, the pump heads were dissected to explore thrombosis. Results: Platelets decreased in the first 72 h and returned to the baseline at the 120th hour. The neutrophils increased in the first 24 h and returned to the baseline at the 48th hour. Factors II, VII, and X decreased in the first 24 h and gradually increased, while factors VIII, IX, XI, and XII decreased in the first 24 h and remained at a low level. The baseline antithrombin was 73.2 ± 14.4% and reduced to 42.6 ± 9.9% at the 168th hour. Pathology showed seven sheep developed thrombus, but no clinically relevant bleeding or thrombosis events occurred. Conclusions: The study explored hemostatic alterations during ECMO in healthy animal models, which eliminated the confounding under critically ill conditions. The study may provide insights into ECMO hemostatic disorders and aid the design of optimal therapeutic strategies. Abstract :